Drought impacts on tree phloem: from cell-level responses to ecological significance. (6th February 2019) - Salmon, Yann; Dietrich, Lars; Sevanto, Sanna; Hölttä, Teemu; Dannoura, Masako; Epron, Daniel
Abstract: On-going climate change is increasing the risk of drought stress across large areas worldwide. Such drought events decrease ecosystem productivity and have been increasingly linked to tree mortality. Understanding how trees respond to water shortage is key to predicting the future of ecosystem functions. Phloem is at the core of the tree functions, moving resources such as non-structural carbohydrates, nutrients, and defence and information molecules across the whole plant. Phloem function and ability to transport resources is tightly controlled by the balance of carbon and water fluxes within the tree. As such, drought is expected to impact phloem function by decreasing the amount of available water and new photoassimilates. Yet, the effect of drought on the phloem has received surprisingly little attention in the last decades. Here we review existing knowledge on drought impacts on phloem transport from loading and unloading processes at cellular level to possible effects on long-distance transport and consequences to ecosystems via ecophysiological feedbacks. We also point to new research frontiers that need to be explored to improve our understanding of phloem function under drought. In particular, we show how phloem transport is affected differently by increasing drought intensity, from no response to a slowdown, and explore how severe drought might actually disrupt the phloem transport enough to threaten tree survival. Because transport of resources affects other organisms interacting with the tree, we also review the ecological consequences of phloem response to drought and especially predatory, mutualistic and competitive relations. Finally, as phloem is the main path for carbon from sources to sink, we show how drought can affect biogeochemical cycles through changes in phloem transport. Overall, existing knowledge is consistent with the hypotheses that phloem response to drought matters for understanding tree and ecosystem function. However, future research on a large range of species and ecosystems is urgently needed to gain a comprehensive understanding of the question.